The use of special economic zones to drive sustainable development in Egypt: A case study on the Suez Canal region - Ali, Dona Alaa (AUC Knowledge Fountain, 2020)
One major problem facing Egypt is improper allocation of the country’s resources that potentially enhancing Egypt’s development. The Suez Canal Zone is one of these misused resources. In recent years, the Suez Canal area has not been efficiently exploited in parallel to its geographical importance in the world trade route. Thus, it is essential to set a sustainable development strategy and implemented it properly in order to upgrade this area and reap its potential advantages which may contribute to the country prosperity. Unless the Suez Canal region is efficiently managed, Egypt risks losing valuable development opportunities. This research argues that Special Economic Zones (SEZs) could offer a successful way to drive sustainable development in the country, provided this economic zone is appropriately established and customized to fits Egypt needs. The concept of SEZs is gaining global recognition and acceptance, particularly since its successful performance in the Asian Tigers countries, amongst others. Despite these achievements, SEZs in certain developing countries have negatively impacted on the sustainable national growth. Because there is no unified model to suit every situation, it is essential to plan a well-defined framework in the Suez Canal economic zone (SCZone) that supports inclusive growth in Egypt generally and in the Suez Canal region particularly. Such a framework could be built around a long-term commitment which supports economic growth in Egypt, relying on solid social and environmental standards. This dissertation focused on analyzing the role of the current Egyptian special economic zones in achieving its objective, and accordingly proposed a sustainable strategy that supports Egypt vision 2030 in the SCZone. Ultimately, this dissertation found that during 2002-2018 period, SEZs in the Suez Canal region have a significant positive impact on the economic growth whereas they have a significant negative effect on the social and environmental standards. Thus, for making growth more inclusive, the government should have more responsibility for improving the human capital and supporting clean production practices in the SCZone.